Seasonality and post fire recovery in a wetland dominated region: Insights from satellite data analysis in northern Argentina - Saucedo, Griselda Isabel; Kurtz, Ditmar Bernardo (Elsevier, 2025)
Scientific literature indicates that climate change is driving an increase in wildfires globally. This study was done on a wetland dominated area in Northern Argentina and aims to, i) analyze the monthly and annual variability of burned areas between 2001 and 2022; ii) identify the fire frequency considering inter annual variability; iii) characterize the frequency of fires by season and the affected vegetation cover; and iv) evaluate the ecosystems recovery following the mega fire events of 2022. We found that 80,728 km2 burned during the study period, with a seasonal concentration of patchy fires at the end of winter. However, larger burned areas were observed in summer, following dry periods. The highest concentration of burned areas was recorded in the central-east and northwest of the province. 71% of the burned areas experienced at least one fire, while 29% showed increased recurrence. Differences in fire activity based on vegetation cover and seasonal changes revealed that grasslands and wetlands are particularly prone to burning during the summer and winter. The atypical fires of 2022, which coincided with the peak of the growing season, caused phenological shifts of the typical vegetation pattern. Likewise, an analogous pattern was observed in unburned vegetation, attributable to the prevailing climatic conditions. Post-fire precipitation spurred on vegetation recovery depending on the prevailing land cover as follows, grasslands, wetlands, and native forests showed exponential post-disturbance recovery, characterized by an initial rapid recovery phase. In contrast, cultivated forests exhibited very low recovery. As climate change trends intensify in the future, anthropogenic and natural wildfires may exhibit varying impacts on different types of land cover. This research provides novel insights into the spatial and temporal variability of fires and recovery dynamics for the region.